Reasonable Trust. (17th February 2011) - Simpson, Evan
<x xml:space="preserve">Abstract</x> Abstract: Establishing trust among individual agents has defined a central issue of practical reasoning since the dawning of liberal individualism. Hobbes was convinced that foolish self‐interest always threatens to defeat uncompelled cooperation when one can gain by abandoning a joint effort. Against this philosophical background, scientific studies of human beings display a surprisingly cooperative species. It would seem to follow that biologically inherited characteristics impair our reason. The response proposed here distinguishes rationality and reasonableness as two forms of good reasoning. One is consistent with the model of strategic rationality, the other with a model of emotional relationship. From the Hobbesian perspective trusting agents are not rational if their makeup discourages advantageous defection even when one knows it will not be detected or punished. The point is indecisive because reasonable trust insulates cooperative action from the factors that have appeared to make it chancy or unstable without some enforcing power. A critical theme is that trust does not simply rest upon a biological disposition to conform to norms. That would explain but not justify aversion to defection. In fact, trust can survive reasoned challenges to norm‐conforming dispositions, displaying the responsible social animal living along with the rational individual.